KAJIAN STILISTIKA CERPEN â€œJALAN GELAP LANGIT TERANGâ€ KARYA ABDUL WACHID (Stylistics Study of Abdul Wachidâ€™s Short Story â€œJalan Gelap Langit Terang") - Isro, Zuyinatul (ALAYASASTRA, 2019)
This research discusses imagery, diction and figure of speech in a short story entitled ?Jalan Gelap Langit Terang? written by Abdul Wachid. This short story is one of the author?s works in a short story anthology, Bacalah Cinta, published by BukuLaela in 2005. This research reveals some figure of speeches such as diction, imagery and elaboration employed by the author of the short story. This research applied both stylistic approach and descriptive qualitative method. Data collection was done by close reading observation and note taking. The result shows that the author takes the advantage of connotative, English and Indonesian diction in some sentences. The imagery employed by the author covers personification, hyperbole, metaphor, repetition, rhetoric, elypsis, and antithesis. Moreover, the author tends to show repetition and symblolism in his style.